Diagnostic accuracy of MRI with metal artifact reduction for the detection of periprosthetic joint infection and aseptic loosening of total hip arthroplasty. Issue 131 (October 2020) - Schwaiger, Benedikt J.; Gassert, Florian T.; Suren, Christian; Gersing, Alexandra S.; Haller, Bernhard; Pfeiffer, Daniela; Dangelmaier-Dawirs, Julia; Roski, Ferdinand; von Eisenhart-Rothe, Rüdiger; Prodinger, Peter M.; Woertler, Klaus
Highlights: Artifact-reduced MRI improves imaging of total hip arthroplasty. MRI was accurate for the diagnosis of periprosthetic joint infection. MRI can be a useful tool especially in inconclusive cases. Abstract: Purpose: To evaluate imaging characteristics obtained from magnetic resonance imaging (MRI) with metal artifact reduction (MAR) to differentiate between periprosthetic joint infection (PJI), aseptic loosening and cases without these pathologies after total hip arthroplasty (THA). Methods: Patients with THA (n = 41; mean age 66.4 ± 9.6 years; 25 women) undergoing 1.5 T MRI with high-bandwidth sequences and view angle tilting followed by revision surgery within 3 months were identified retrospectively. Imaging findings at the metal-bone interface, in the surrounding bone, the soft tissues and lymphadenopathy were assessed by three radiologists in a standardized fashion. Based on clinical and intraoperative findings, patients were categorized in groups with PJI (n = 15), aseptic loosening (n = 15) or without these pathologies (n = 11). Imaging findings were assessed in crosstabs, receiver-operating characteristics and classification and regression trees. Results: Findings at the acetabular cup were specific for the presence of either PJI or aseptic loosening (specificity>0.765 for all), while findings at the stem were sensitive (sensitivity>0.824 for all except periostitis). To differentiate PJI versus aseptic loosening, soft tissue edema (sensitivity, 0.867/specificity>0.733), abnormalities at both, acetabular and femoral components (0.667/0.933–1.000) and enlarged lymph nodes (0.800/0.867) were accurate. Conclusion: Standardized assessment of MR imaging findings in THA patients facilitated the differentiation of PJI and aseptic loosening. This information can be helpful for therapy planning.